Eksistensi Penyuluh Pertanian dalam Pelaksanaan Komunikasi Pembangunan Partisipatif untuk Keberdayaan Petani - Jaya, Muhammad Nur (JURNAL AGRIBISNIS TERPADU, 2018)
Agricultural development continues to develop in tune with the development of agricultural innovation technology. In line with this, farmers are required to increase competitiveness in this era of globalization, therefore it is important to use participatory agricultural development communication by prioritizing local communities with their cultural dimensions as holders of power. The new communication paradigm places farmer groups as subjects of development that were previously always the object of development, the focus of agricultural development is directed at local communities. Agricultural instructors in their activities as agents of change in development always provide direction that can awaken the awareness of the farming actors. In addition, agricultural extension agents provide a forum or facilitate farmers to conduct training in the field of rice farming management, in particular the use of agricultural technology with innovation that can lead to increased productivity of processed rice products. The aim of this study: 1. Analyzing the role of agricultural extension agents in their existence in increasing agricultural development for the empowerment of farmer groups ? 2. Analyzing the relationship between agricultural extension officers in the implementation of participatory development communication for the empowerment of farmer groups. This study uses the positivistic paradigm using the survey method. Quantitative research is carried out in two districts in 8 sub-districts which are the object of research or unit of analysis, is a farmer group by taking a sample of 170 farmer groups. The research data were analyzed descriptively and explanatively. The results of the study are: a. The overall role of agricultural extension agents is in the high category; b. There is a significant correlation between agricultural extension and the implementation of participatory development communication.